Worry effect for COVID-19 transmission over depression, anxiety, and satisfaction with studies in Peruvian university students - Mamani-Benito, Oscar; Carranza Esteban, Renzo Felipe; Castillo-Blanco, Ronald; Lingán-Huamán, Susana K.; Gálvez-Díaz, Norma del Carmen; Huancahuire-Vega, Salomón; Corrales-Reyes, Ibraín Enrique (Frontiers in Education, 2023)
Concern about contracting COVID-19 has had repercussions on university students. The aim of this study was to determine its effect on depression, anxiety, and satisfaction with studies. Using an explanatory cross-sectional design, 1260 medical, nursing, and dentistry students from both public and private universities in Peru participated. They were assessed using a scale for concern about contracting COVID-19, the Patient Health Questionnaire-2, the Generalized Anxiety Disorder-2 (GAD-2), and a brief scale for satisfaction with studies. After analyzing the data using structural equation modeling, it was found that the explanatory model had an adequate fit. It showed that concern about COVID-19 has a direct and significant effect on anxiety (β=0.46, p<0.001) and depression (β=0.38, p<0.001). However, the same effect was not evident on satisfaction with studies (β=-0.06, p=0.068). In conclusion, the uncertainty about contracting COVID-19 triggered symptoms of anxiety and depression among Peruvian university students. Still, it did not affect the satisfaction students felt when their academic expectations were met.